Identification of exosome miRNAs regulated by SPHK2 in human glioma cells - Liu, Jing; Zhao, Huafu; Liu, Xia; Guan, Xiaoyun; Guo, Qiyu; Xu, Yanwen; Qiu, Jinhua (Frontiers in Oncology, 2025)
BackgroundGlioma is the most common primary brain tumor, and the WHO 4 glioma, glioblastoma (GB), is a malignant tumor with high invasiveness and mortality. Tumor-associated macrophages (TAMs), as the main immune cells in glioma, play an important role in the growth, invasiveness, immune escape, and drug resistance. The M2 phenotype of macrophages, but not the M1 phenotype, promotes glioma development. Recent studies have shown that sphingosine kinase 2 (SPHK2) is positively associated with TAM infiltration and glioma proliferation. SPHK2-deficient tumors showed impaired growth and failed to polarize macrophages toward an M2 phenotype.ObjectiveOur aim was to reveal whether SPHK2 affects exosome microRNA (miRNA) release from glioma cells and which miRNAs regulated by SPHK2 could mediate the polarization of macrophages around glioma cells.MethodsSPHK2 knockdown of the human glioma cell line U373 was performed using short hairpin RNA (shRNA) lentiviruses. Exosome miRNAs were isolated and evaluated using RNA sequencing (RNA-seq). Gene Ontology (GO) analysis was carried out to determine the function of exosome miRNAs targeting genes. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was used to view the pathways of these genes.ResultsWe successfully isolated exosomes from the U373-HK and U373-SH glioma cell lines. We found 12 exosome miRNAs differentially expressed between U373-HK and U373-SH cells. The heatmap showed two upregulated and 10 downregulated miRNAs in glioma cells with SPHK2 knockdown. There were 12 miRNAs targeting genes assigned to 118 GO terms, including 53 biological processes, 30 cellular components, and 35 molecular function terms. KEGG mapping further clustered several signaling pathways, such as “Wnt signaling,” “p53 signaling,” “proteoglycans in cancer,” and “cell cycle.” “Wnt signaling” was identified as the most significantly enriched pathway in the KEGG analysis. A total of 17 genes were enriched in this pathway.ConclusionsThe present study elucidates that SPHK2 promoted the release of 10 exosome miRNAs, but inhibited the release of two miRNAs. The KEGG data indicated that these miRNAs targeted several important genes of Wnt signaling. This study provides not only a genomic resource for further studies but also novel insights into uncovering the molecular mechanism of SPHK2 regulating M2 TAM polarization.